Program zdravstvenega izobraževanja sladkornih bolnikov - Starc, Andrej (Obzornik zdravstvene nege, 2003)
The article deals with health education program for diabetes patients in the clinic for diabetes. Health education of diabetes patients should be based on adult education principles. The study used descriptive causal non-experimentalmethod-case study and was conducted from October 2001 to January 2002.
Keywords: bolniki; Diabetes Mellitus; Health Education; Sladkorna bolezen; Zdravstvena vzgoja